Control of IGFBP-2 expression by steroids and peptide hormones in vertebrates - Andreas eHoeflich; Elisa eWirthgen; David eRobert; Carl Friedrich eClassen; Marion eSpitschak; Julia eBrenmoehl (Frontiers in Endocrinology, 2014)
IGFBP-2 (1) has been described as a brain tumor oncogene (2) and is widely expressed in cancers from different origins (3-8). IGFBP-2 alone cannot cause malignant transformation, yet progression of brain tumors to higher grade (9) and even has been provided as a protective element in earlier stages of multistage colon carcinogenesis (10). Therefore, it is crucial to understand the factors that determine expression patterns of IGFBP-2 under normal and malignant conditions. The present review provides a comprehensive update of known factors that have an impact on expression of IGFBP-2.